Father’s and Son’s Courage in Cormac McCarthy’s The Road (LITERA KULTURA : Journal of Literary and Cultural Studies, 2014)
Father’s and Son’s Courage in Cormac McCarthy’s The Road Mohammand Faiz, Sastra Inggris, Fakultas Bahasa dan Seni, UNESA Prof. Dr. FD Kurnia, M.Pd., Sastra Inggris, Fakultas Bahasa dan Seni, UNESA Abstrak Life is the gift that the God gives the human, where there are many challenges and problem that the human have to face in it. In doing the life human needs courage in order to be able to handle every challenges and problems that comes to them. There are many kinds of problem in the life; family, social, economy, or even disaster that can destroy the earth such as described in Cormac McCarthy’s The Road where the environment is devastated because of disaster and earthquake. This devastation causes great damage and also makes many creatures dead. It surely makes people who live in the devastation of earth find difficulty in doing the life because of little food, supplies and also the air is unclean because it is filled by ash and dust, especially the main character the father and the son. It forces them to struggle for survival and to stay alive. They have to keep trying to find food, water or place to survive. There for, there are some problems about how the courage describes in the novel, which are delivered to two main questions of (1) How is father’s and son’s courage in Cormac McCarthy’s The Road? And (2) How is the impact of their courage to themselves? In analyzing the problems, the writer uses psychoanalysis theory by Sigmund Freud to know how the courage happens to the main character and also the theory of courage including its types. To get a clear analysis, this research uses descriptive quality method. It means the quality of data becomes the reference of the work rather than the quantity of the data. So, it is clearly seen how their courage is in struggling to survive from the ruined world. They have to undergo the hard life; hard to breathe, hard to find food and they are always hunted by the fear of the devastation of earth’s threaten. And with the courage, they can survive and stay alive because the courage has given strong stance, confidentiality, faith, spirit and power to struggle for survival from the devastation of earth. Keywords: Psychoanalysis, courage, physical courage, moral courage. Abstrak Hidup adalah hadiah yang tuhan berikan kepada manusia yang mana di dalamnya terdapat banyak tantangan dan masalah yang harus dihadapi. Dalam menjalani kehidupan manusia membutuhkan keberania agar bisa menghadapi tantangan dan masalah yang datang. Ada banyak macam permasalahn yang ada dalam kehidupan; masalah keluarga, sosial, ekonomi atau bahkan bencana yang bisa menghancurkan bumi seperti yang terjadi dalam novel The Road karya Cormac McCarthy yang digambarkan seluruh lingkungan musnah karena bencana dan gempa bumi. Kehancuran tersebut menyebabkan kerusakan yang luar biasa dan juga menyebabkan banyak makhluk hidup yang mati. Hal itu tentunya membuat orang-orang yang hidup dalam kehancuran bumi tersebut merasa kesulitan dalam menjalani kehidupan karena persediaan makanan yang sedikit dan juga udara yang tidak bersih karena abu dan debu, terutama tokoh utama, ayah dan anak. Hal itu memaksa mereka untuk berjuang bertahan hidup. Mereka harus tetap mencoba untuk bisa mtempatendapatkan makanan, air dan tempat untuk berlindung. Oleh karena itu, ada beberapa masalah tentang bagimana keberanian digambarkan dalam novel tersebut, yang kemudian memunculkan dua dasar pertanyaan (1) Bagaimana keberanian ayah dan anak digambarkan dalam novel The Road karya Cormac McCarthy? dan (2) Bagaimana dampak keberanian bagi diri mereka sendiri. Dalam menganalisis permasalahan tersebut, penulis menggunakan teori psikoanalisis oleh Sigmund Freud untuk mengetahui keberanian yang terjadi pada tokoh utama, dan juga menggunakan teori keberanian dan tipe-tipenya. Untuk mendapatkan analisis yang jelas, skripsi ini menggunakan metode descriptive quality dimana kualitas data menjadi poin utama daripada jumlah data. Jadi, terlihat jelas bagaimana keberanian mereka dalam berjuang untuk bertahan hidup dalam kerusakan dunia. Mereka harus menjalani kehidupan yang sulit; sulit bernafas, sulit mendapatkan makanan dan mereka juga selalu dihantui oleh rasa takut akan ancaman-ancaman dari kehancuran bumi. Dan dengan keberanian, mereka bisa bertahan hidup, karean keberanian tersebut telah memberikan pendirian yang kuat, kepercayaan diri, semangat dan kekuatan untuk bertahan hidup dari kehancuran bumi. Kata kunci: Psikoanalisis, keberanian, keberanian fisik, keberanian moral. introduction Everybody must have ever heard of courage, but some of them do not know what the courage is. According to the Advanced American Dictionary, courage is a “quality of mind or spirit that enables one to face danger, fear, or vicissitudes with self-possession, confidence, and resolution.” This all suggests that the quality of courage allows the human being to face life, especially in the moments where someone can experience fear or danger. Courage is so important for people, because with courage people will have a strong stance for doing something. Samuel Johnson said “Courage is the greatest of all the virtues, because if you haven't courage, you may not have an opportunity to use any of the others” (Raymond E. Beckham, 2006: 91). Courage is indeed very important thing, and people must have bravery or courage because it can influence the success of people. Everything will lose without courage. Life is the most beautiful gift the God has given the human. Samuel Butler said in Vincent Vinci that Life is the art of drawing sufficient conclusions from insufficient premises (2000:64). But, life is not as easy as spoken, because life offers everything for people. There are many problems the people must face, and the problems are also varied. There are trivial problems and also complicated that it is difficult to solve and it certainly needs courage to confront them. The novel entitled “The Road” is a novel that adapts the topic of courage and strength. This novel is created by Cormac McCarthy. Cormac McCarthy is an American writer. He finished in writing The Road in 2006. The Road is Cormac McCarthy's most recent novel, describes the bleak journey of a father and son across a post-apocalyptic American landscape. He was visiting El Paso, Texas, with one of his sons, John Francis McCarthy, in 2003 when the initial idea for The Road was born: McCarthy envisioned how the city would look in the future. McCarthy dedicated this novel to John. This novel describes the hardship of two people, father and son, who struggles to survive in the devastation of earth. The author shows the courage when he takes you on a journey of them through a ravaged landscape through their heartfelt story. They struggle to survive in the harsh weather with little food, supplies, or shelter. The story describes the journey south after an unnamed catastrophe that struck the world. The man and the boy, who also remain unnamed throughout the entire novel, travel through the rough terrain of the southeastern United States. The conditions they face are unforgiving: rotted corpses, landscapes devastated by fire, abandoned towns and houses. These two travelers are among the few living creatures remaining on earth that have not been driven to murder, rape, and cannibalism. This article has two related research goals that will be discussed and explained. The first is to describe father’s and son’s courage in Cormac McCarthy’s The Road. The writer will give a describing how the father’s and son’s courage in the novel. The second is to reveal the impact of father’s and son’s courage to themselves in Cormac McCharty’s The Road. This article will give the information about the impact of their courage to themselves. “The Road” is a great novel. McCarthy does a wonderful job at the beginning to bring you into the story. He provides you with immense detail to paint a gray and mystic scene. He continuously provides details of the surroundings to keep you interested. Complementing the immense detail is an extraordinary story line. Not only that, but the novel has also met with great critical success. In 2006, McCarthy was awarded the James Tait Black Memorial Prize in fiction, the Believer Book Award and was a finalist for the National Book Critics Circle Award for fiction. On April 16, 2007, the novel was awarded the 2007 Pulitzer Prize for fiction. In 2012, it was shortlisted for the Best of the James Tait Black. McCarthy's literary repertoire includes revisions of various genres, including the crime thriller (No Country for Old Men) and the Western (the Border Trilogy). Some readers entertain an ongoing debate regarding whether The Road should be classified as fiction, science fiction, or even horror, given McCarthy's brutal prose and unflinchingly vivid vision of what could be considered a hell on earth. Nonetheless, most people agree that The Road is a deeply moving, if also deeply disturbing, work of unparalleled literary genius that transcends any discussion of genre. In analyzing the novel, the article uses psychoanalysis theory. It is because the topic is about psychology. Psychoanalysis is a method of investigating and treating personality disorders and is used in psychotherapy. According to Ernest Van Den Haag, Psychoanalysis refers to Freud techniques of investigation which he was led by the use of his method, and finally to a treatment of personality disorders which uses the method and the theory. (1963: 24). The psychoanalysis that is used is Sigmund Freud theory. They are Id, Ego and Super-ego. Frank Tallis (2002: 61). The first and the oldest agency of the apparatus is called the id, where the instincts come from and to every living creature. Id contains the demand of basic biological needs of life; food, sleep, sex, and more. It is the only component of personality that is present from birth. It operates unconsciously, and its principle function is to bias mental life in such a way as to engineer the discharge of libido. The ego has conscious, preconscious and unconscious. It has a largely managerial function in initiating and monitoring thought and movements. He also said that the ego develops from the id and ensures that the impulses of the id can be expressed in a manner acceptable in the real world. So, the ego deals with the reality. After the id and the ego, there is a third power which the ego must take in the consideration. It is called super-ego; parental and external influences to the ego. The development of the super-ego occurs in the long period of childhood during the influences of the parents and continue along contributions come from others. In an action, the ego must satisfy the id and the super-ego and also aware of the external condition and reality. Super ego is the aspect of personality that holds all of the internalized moral standards and ideals that acquire from both parents and society. It refers to the sense of right and wrong. The superego also has conscious, preconscious and unconscious regions. But the function is to act as moral judge or making judgments. The article is also used the theory of courage and its type. According to Gelven in Mufid James Hannush (2002: 107) “courage is the ability to endure the tension between the opposing forces of attraction or repulsion. . . what repels is the fear of pain, what attracts is the lure of significance and wholeness”. From the theory above can be concluded that courage allows a person to engage life’s challenges and problems, stresses and storms, in spite the fears, weaknesses, and imperfections, without losing the existential worth. Commonly, courage is divided into two different types. They are physical courage and moral courage (Jerry A. Webster, 2012: 64). Daniel A. Putman said that physical courage is the ability to overcome a fear of death or physical harm (2004: 1). From the definition, it can be concluded that physical courage has two components. They are fear of death (Thanatophobia) and physical harm. Fear of death or it is known as Thanatophobia is one of the most universal fears, and maybe the basis of phobias. The term "physical harm" as used in the Act and this part means any physical injury to the body, including an injury that caused, either temporarily or permanently, partial or total physical disability, incapacity or disfigurement. Moral courage is the ability to act rightly or to take action for moral reasons despite the risk of adverse consequences. Moral courage can be called as a virtue with preservative powers. According to Richard M. Gula (2007: 122), there are three elements defining moral courage: fear in the face of a threat, a willingness to endure danger, and standing up for the values. METHOD In collecting data, the writer reads the novel The Road to get information of the novel, because the novel is the main data of the research that is going to analyze by the writer. Another data is also gotten by reading library book, article, essay, bibliography, and browsing the information through internet to support the explanations of related topic. After the writer gets the data, so the data is analyzed nad discussed in accordance with the background of study and statements of problem. In giving explanation about the analysis, the plot of the story will be explained and told first in order the reader can understand how the story is and then the analysis will be explained after telling the plot of the story by using qualitative sentences. After all data is analyzed, the conclusion will be made based on the explanation. The writer organizes the research into four chapters. The first chapter is introduction. In introduction, the writer explains about the background of study, statement of problems, purpose of study, significant of study, scope and limitation of study, research method and technique of presentation. The second chapter is review of related literature that will clarify the psychoanalysis, the theory of courage and the types of courage. The third chapter deals with the analysis which consists of father’s and son’s courage and the impact of father’s and son’s courage. And the last chapter namely the fourth character is conclusion and suggestion about the research. DISCUSSION Father and Son’s Courage Courage is one of the most important components in human’s self, because by having courage people will not be doubt to do something. As Maya Angelou said that courage is the most important of all virtues, because without courage people can’t practice any other virtue consistently. People can’t practice any virtue erratically, but nothing consistently without courage (J. Pincott, 2010: 35). The novel entitled “The Road” is an inspired novel that tells about the struggle of two people, the father and his son, in surviving life from devastation of earth. It is described that the environment was very dirty. The air was filled by the ash and dust forces them to wear a mask. The weather extremely changes a while. Few days were raining, and another was snowing. It makes the father and his son have to worry their life. The unfriendly weather makes them worry about many things, mostly they worried about shoes. Worrying is something that the father and his son have to do. There is no certainty living in such ruined world. It is a common thing for them to worry anytime and it is not surprised thing. The weather is extremely cold. It is not surprising that the weather turns to colder and colder. The weather has changed anytime; sometime it rains and often snow. It is why they had to worry about shoes and also clothes. Shoes keep the father and his son feet to keep away from coldness and freezing which can take their life. Not only worrying about shoes and clothes, but also worrying about food. Food is essential thing to keep alive. It is the reason why they worry of food. If they can’t find some foods, it means they will die. And the shoes are important to hold a journey in looking for food. The coldness of weather doesn’t only force them to eat the food that already fermented but also threaten their life. The coldness is very extremely danger for them. Moreover it is described that the cold can crack the stone and takes their life off. In such condition surely makes them hard to breathe because in the coldness the air contains thin oxygen. Besides the shoes and the food, they also have to find a safe place to take a rest. Dwelling the life in the ruined world with little food, supplies, or shelter force them to travel the road everyday and every time for finding food to survive. It surely makes them very tired and need to take a rest and sleep. They have keep going and struggle to stay alive. They have also to avoid the murderers and cannibalisms because they can take their live off anytime. Struggle is a must to do to find another thing to be eaten and avoid from other threatens to keep the life. Keep trying is the key for the good guys who living in the ruined environment to survive. By keeping trying, they can survive dwelling the life in such environment. Keep trying is not enough to live in such devastated earth. Always suspect the possibility that may happen has to be done, because no one knows what will happen, but the threat of nature always happen all the time. Facing many kinds of challenges and threatens in the destruction of earth is not certainly easy. The courage must be kept in their soul because it is the most important thing to make them keep spirit in enduring the life. They must be able to fight with the fear and lose them because it will be a reason they stop struggle. They must really struggle and never give up to be able staying alive in such condition. They have to fulfill the basic biological needs of life such as food, sleep sex and more. It all is the demands of their id and they have to fulfill because it is very important especially the food. As explained in the second chapter that id is a gift given since the birth of human where it contains the demand of basic biological needs. It is the source of passion. In the story, the father and his son were suffered with the little food and clean water. So they have to struggle to satisfy their biological need of life. From all the explanation as above, the father and the son courage is described to struggle in surviving from the devastation of earth, fulfilling the basic needs and also avoiding and escaping from the murderers and cannibalisms. They have to keep trying over and over again to stay alive. ANALYSIS Father’s and Son’s courage Father’s Courage His courage appears when he decides to reject his wife’s request to commit suicide and chooses to survive. His wife is insistent to do it because she is desperate and nothing can be done. The condition makes her want to end her life. But character father always tries to stop her bad decision. “You mean you wish that you were dead?” “Yes” “You mustn’t say that” “But I do” “Don’t say it. It’s a bad thing to say” “I can’t help it”. (P. 55) The father is so suppressed facing his wife with her stupid decision. He has to make his wife sure that everything will be all right. Besides he still have a son and the son still needs parents so much. The father is worry about his son because he is still young, he still needs his and wife’s affection. This unfriendly condition has broken the life in the world. There is no sign of life in it because everything is destroyed by the great disaster. In this situation, the father has tried to manage and monitor his wife’s id that wants to end her life. The father has tried to convince her wife’s bad and crazy decision. He knows that suicide is a bad act so that he wants to fail what his wife will do. We can see that the father’s courage is so great. He is brave to bear all responsibility alone because his wife has left him. He is able to endure the tension between him and his wife and has done a good deed in his life. He has tried to stop a bad deed that his wife will do. What he has done is a moral act and also moral courage. Moral courage is ability to act a rightly and what the father does is a right thing. He holds on to the rightness. The father has done everything rightly and morally. He has a good self-control, as the result he can manage everything bravely with the right decision and not influenced with his wife’s request. He has done moral deed where it is called super-ego. As we know that super-ego refers to the right and wrong and the ego of the father has satisfied the need of super-ego that is acts rightly based on the moral standards. In the case, the father’s moral courage can be categorized to the standings up for the values. It is because he knows that suicide is a bad thing and it is not appropriate with the moral standards. Therefore he wants to fail it bravely. Another event that shows about father’s courage is when he met the bad guys. At that time, they were sleeping on the leaves and they came. Something woke him. He turned on his side and lay listening. He reached his head slowly, the pistol in his hand. He looked down at the boy and when he looked back toward the road the first of them were already coming. (P. 60) The father’s courage is shown when he was brave to threaten one of them who standing twenty feet away from his position. He threatens to kill the man by cocking the pistol on the men. What the father does is very dangerous indeed. It can endanger himself and his son. The father’s action is very dangerous, but he knew that no other way to be done. If he did not do it and just silent, the bad guy could see and kill him and son, and if he went away directly, the bad guy would certainly see and the father could be shot or they would hunt him. From the explanation above we can see how great the father’s courage. He is willing to do everything to protect his son. He doesn’t want someone touches and hurt him. The courage that the father shows in that event is a moral courage. As explained in the chapter two that moral courage can be defined from three elements; fear in the face of threat, a willingness to endure danger and standing up for the values. In the case, the father’s moral courage can be categorized to number one and two. It is called the fear in the face of threat because he is in the great dangerous condition. We know that they face a great threat and He is very scared. Facing such condition is not easy. But the father is brave to fight with the fear. When he meets one of the bad guys, the father has to decide to fight with him because there is no other way except fighting him. It has been indicated that he is brave to face the fear of threat. It is clearly defined how he acts and takes decision in the condition bravely. He is forced to be brave and faces the fear to escape from the bad guys. Confronting such condition surely makes our mental suppressed. The fear will cover our mind and thought nonsensical. But if we have courage, everything will be easy as the father shows in the story. The father’s courage when facing that condition can also be categorized into a willingness to endure danger. It is clearly defined that the condition is very dangerous and he and his son stands up in that danger. He had to confront the threat that can take his life off. As we know that protecting his son is his job and he really doesn’t want someone, especially bad guy touch him. By having willingness to protect the son especially in such condition, it means that he has also has willingness to endure danger because he will do anything to make his son safe and not be hurt by bad guys. Another courage the father shows is when he passes the last of the sad wooden buildings. The father feels there is something whistles past his head and clattered off the street and broke up against the wall of the block building on the other side. Then he sees a man in upper window of the house drawing a bow on them and then the father pushed the boy’s head down and tried to cover him with his body. And bow hit his leg. He heard the dull thwack of the bowstring and felt a sharp of pain in his leg. Oh you bastard, he said. You bastard. (P. 263). The father is willing to sacrifice his soul to protect his son by covering him with his body when the bow would hit them. It is a very brave action the father does for his son. Knowing his body hit by the bow, the father directly grabbed the flare gun from the cart and chocked it then shot the man. The man fired and couldn’t draw the bow anymore. The flare went rocketing up toward the window in a long white arc and then he could hear the man screaming. We can see how great the courage of the father. The sense of love for the son makes him brave to do everything to protect his son. He sacrificed himself to protect the son. He didn’t care about his body. He just thought to protect the son from danger. The love feeling to the son had aroused the great courage in the soul. He had proven his affection to his son. It is clear that what the father does is a physical courage, it can be seen when he sacrifice himself to save the son. It can make him killed by the bow, but he doesn’t think about his body, he just think to protect his son. But it can also be said the moral courage. It was signed from the wise decision that he took although he has to sacrifice his body. But what he did was really a moral and brave action. Son’s Courage The son’s courage refers to the moral courage. He hardly ever does the action that connects to the physical courage. All action that connects to the physical courage is done by his father. His moral courage is shown by willingness to help everybody he met because of empathy. He always wanted to help someone although he must debate with his father because the father doesn’t agree with his idea. It can be seen when he met an old man and really wanted to help him but the father reject his request. The boy squatted and put a hand on his shoulder. “He’s scared, Papa.” The man is scared. He looked up the road and down. “If this is an ambush he goes first, he said.” “He’s just scared, Papa.” “Tell him we won’t hurt him.” “The old man shook his head from side to side, his finger laced in his filthy hair. The boy looked up at his father.” “Maybe he thinks we’re not real.” “What does he think we are?” “I don’t know.” “We can’t stay here. We have to go.” “He’s scared, Papa.” “I don’t think you should touch him.” “Maybe we could him something to eat.” He stood looking off down the road. Damn, he whispered. He looked down at the old man. Perhaps he’d turn into a god and they to trees. All right, he said. (P. 162). If we see the case and connecting to the Freud’s theory, the boy here is monitoring or managing the id of the father with his ego. The father just thinks about himself and just satisfied his passion where it is called libido. The boy doesn’t only manage the father’s id, but he also satisfies his super-ego in his soul. He does the right thing. The devastation of earth has made him knowing the external world. His ego is formed when he face many challenges with the father. Sometimes the father is very emotional and doing a bad thing to someone else that can make him killed slowly. And the son has to lose his father’s emotion as the event occurred when he reached the man who had stolen and brought his cart. The father was very mad to the man. “If you don’t put down the knife and get away from the cart, the main said. I’m going to blow your brains out……” He laid the knife on top of the blankets and back away and stood. “Back more.” “He stepped back again.” “Papa, the boy said.” “Be quiet.” “He kept the eyes on the thief. Goddamn you, he said.” “Papa please don’t kill the man.” “The thief’s eyes swung wildly.” The boy was crying. “Come on, man. I done what you said. Listen to me boy.” “Take your clothes off.” “What?” “Take them off. Every goddamn stitch.” “Come on. Don’t do this.” “I’ll kill you where you stand.” “Don’t do this, man.” “I won’t tell you again.” “All right. All right. Just take it easy.” He stripped slowly and piled his vile rags in the road. “The shoes.” “Come on, man.” “The shoes.” The thief looked at the boy…… Okay, he said. Okay. He sat naked in the road…. (P. 256). The father had made him suffer because he didn’t have clothes and also shoes. He can dead because of the cold wind in the night, or the sunlight in the day and he also will feel difficulty to walk because of not having shoes, it makes possible he can’t walk and looking for food. He can die slowly As described in the speech, the boy doesn’t really want to hurt someone else although he knows that the man have stolen the cart of him. He wants the father releases and lets him go without hurting the man. But the emotion of the father has been high. He likely cannot forgive the thief. He continuously forces the man to give everything he wears. He asked him to take of the clothes and the shoes. But the son really wanted to help the man. “Let’s go, he said.” And they said out along the road south, with the boy crying and looking back at the nude and slat like creature standing there in the road shivering and hugging himself. “Oh Papa, he sobbed.” “Stop it” “I can’t stop it.” “What do you think have happened to us if we hadn’t caught him? just stop it.” “I’m trying.” (P. 258). The son is little angry to his father. He is disappointed to what the father has done. He felt that the father is far too much. He considers it is too cruel doing it to the man. Then he asked his father to give back what he takes from the thief. He was very pity looking the man naked, raw, filthy and starving. The man just covered himself with his hands and shivering. The son’s courage in the story really shows a moral value. He was brave going against his father to do a good and wise deed by helping the man. He stands for a value. It was really brave deed. In the case, he can face the father’s id although he does it unconsciously. He is able to manage the emotion and passion of his father. He always does a good job for everyone without feeling to hurt him. He does it honestly. The Impact of Father and Son’s courage to Themselves The most important thing of their courage is they can survive from the devastation of earth. They can pass all of challenges and problems in the life. The courage has saved their life from the fear that can make them unsafe. There was an idea to end the life when the father still lived with his woman. She always forces him to end their life because there was nothing else to do in the ruined world. However, the father keep his believe that humans have to struggle. The experience of dwelling the life before the unknown disaster made him stronger. The courage that the father has makes him having a great faith and strong stance to defend his aim to survive although he has to live in the ruined world. Dwelling the life in such condition is a very difficult choice because the possibility of staying alive is little, and only them who have strong stance can survive because they don’t despondent. The character father has had strong stance with not effected by flattery of others. He rejects the woman or the wife’s request to end his life together as done by other families. He has changed the situation and condition and saved his life and his son from committing suicide. He believed there is always way to live if he struggled. Courage has saved his and son’s life from suicide. Living in the earth that full of disaster always makes them worry in enduring the life. Threats and dangers can come every time. They must always wary to the things around them. As the time when they take a rest in the car, unexpectedly there are groups of bad guys looking for food even hunting people to be eaten. With the courage they have, they can save their life from the danger that can take their life. The father is very brave to kill some of them by shooting his head with the pistol. The courage has made them survive. Although the condition is very tragic, they stay to get spirit in living the life. The courage has led to a great spirit in him. Facing the hard condition where there are no food and water is a struggle. They must travel to find the stuff. Because of their courage in walking around the road, trying to enter the house to find something makes them stay alive. They find food in every place that they visit. It is shown when they found the yard and also find the room in the ground all at once. There are many foods in the room. The courage has given the spirit and strong stance for the father to do what he believes. They ignore all the bad thought that will failed their mission to survive. They have lost the fear in their soul. The courage will help someone to confront every problems and challenges. It will help people save from danger. It will give a faith and strength to do anything as the father and son feel. They have passed every challenges that make them having courage and strong faith in facing the life. They believe that human has to struggle. They continuously keep going to find food. They try over and over again to find the place and enter the house without knowing the house is safe or not, one of the examples is when they enter the house where it is the place of the cannibals. Their life is very threatened when they are in that house. They stand in the dangerous place. The cannibals can take their life. They can eat them if they are caught. Actually they are really scared. The fear has covered their soul. But the courage has helped them save from the danger. They can control their soul and then go from the house. Courage will make someone do everything he or she believes and will lose everything if he or she has no courage. As Meguel De Cervantes said “He who loses wealth loses much; He who loses a friend loses more; He who loses courage loses it all” (Larry Chang, 2006: 175). It is clear someone will lose many chances because he or she does not confident. As explained above that courage has two types, they are physical and moral courage. The father and the son have shown both of courage, physical and moral courage although the physical courage is more. But moral courage also gives a good result for them. Most of people believe that a good deed will get a good reply as well and on the contrary. Other people will not mind to help good guy, they will be kind helping someone who has done a good deed and given kindliness to other people. It is the shame with what the son gets. Actually they are followed by the man and his family but the father and the son do not know that there is someone follows them, the man. He always pay attention to what the father and the son do. The man has seen their courage, struggle, faith and good deed they have done. But they don’t realize that they are followed. The father never knows that there is someone followed him because at the end of story he was died leaving his son alone. The man has seen the moral courage that the son did to help someone. Because of that the man brings him with him and his family, the wife, his son and daughter. The moral deed that the son did to help someone gets the shame reply. He is saved by the man because he is a good guy. He always help other people although he has to debate with the father first. The result is the God sends someone to save his life. In conclusion, the courage has given many good impacts for the father and the son. They stay alive in the devastation of earth. They get strong faith, spirit, confidentiality, willingness to endure threat and danger, strong stance and strong soul that make him being out of danger and hunger, and make the son alive until the end of the story although the father finally dead because of the worse health. CONCLUSION The research has discussed about the courage of the main character, father and son from the novel “The Road” based on the statement of the problem. In analyzing the character, the writer uses psychological approach taken from theory of Sigmund Freud. In the research, there are two statements of problem; How the main character’s courage and what the impact of the courage to themselves. Those questions have been answered in the analysis. The courage of the main character has been explained detail based on the theory above. As explained in the review of related literature that courage has two types; physical and moral courage and the study has used those two types in analyzing the main character. As seen in the novel, the earth was broken and the air was filled by the ash and dust. Everything which lay on the surface of the earth covered by darkness as the ash effect, everything stands in the earth turned to be black such as the dead trees which burned by fire forest, and the rain water and snow which fell as gray turn into black in the land. The weather is also extremely cold. It is not surprising that the weather turns to colder and colder. The weather has changed anytime; sometime it rains and often snow. The father’s and son’s courage can be seen from their struggle in surviving in the harsh weather with little food, supplies, or shelter and also escape from the cannibals and murderers. In the research, the study gets the difference of the father and son’s courage. The father’s courage refers to the physical and moral courage. There are many challenges and dangers he has to face and confront with his son. The physical courage can be seen when he has to face the danger himself because the boy is still child. The physical courage can be seen when he meets the groups of bad guys. At that time they are in a very dangerous situation. But the father can save his and his son’s life from the bad guys. It can be seen when his boy is grabbed by the man with the knife on his throat and the father directly shoots him with the pistol and goes away. Another case is when he sacrifices his body to protect his son from the bow that causes his body hurt. The moral courage can be seen when he is willing to face the threat and danger as the explanation of moral courage. It is different from the father. The son’s courage also refers to the moral courage. As we know that the boy is still child and cannot face the difficult problem, he still needs the father’s help. So it is logic that his courage is not physical courage. The son’s moral courage is shown when he does goodness to someone else. He always wants to help another one though he himself is starving. The father always disagrees with his idea to help someone, giving them some food of him, but he always opposes and sometimes forces the father to help someone. It can be seen when the cart is stolen by the man and the father is very angry. At the time, the father makes the man leave and give all he has including the clothes. With such condition where the weather is extremely cold, he can be killed slowly because of cold and he cannot also walk away to find food because he has no shoes. The father gets angry so much to the man. But the son asks the father not to do it to the man because it can endanger the man’s life. He continuously forces his father to give back the clothes and the shoes although he has to debate with the father. Finally the father follow what the son asks by giving all he has taken from the man although they don’t met him anymore when they want to give them back, clothes and shoes to the man. But the son put them in the place where he met the man the last time. In the second explanation, the study discusses about the impact of their courage to themselves. The most important impact of their courage is they can survive from the devastation of earth. The courage has saved their life from danger. The numbers of problem and challenges make them always struggle to survive and stay alive. The courage has given a confidential to struggle and keep trying over and over again. The father is always sure to decide and do something best for survival. The confidentiality makes them get spirit to live the life although in the ruined world. The courage also gives the strength to them, the strength to pass the hard life. This strength makes him strong. It can be seen when the wife has idea to commit suicide. She asks the father to end the life together with the son as well. She is really disparate because of the tragic condition. There is nothing to do to survive because she thinks that the bad guys will grab, catch and kill them soon. The earth is broken indeed and it has possibility to make people suffered because there are no food, water and difficult to find a safe place to escape from the cannibals and murderers. But it doesn’t make the father disparate. He is not influenced by the wife. He stands to what he believes. The courage has made him strong. He rejects his wife’s request and decides to live with his son. In conclusion, the father’s and son’s courage is the courage of struggling to survive from the devastation of earth. They have to travel to find food and place to stay alive. The courage also has given many impacts to them. It gives confidentiality, spirit, strength and strong stance that make them survive and stay alive and also save someone else. The willingness to help someone has saved the son’s life although the father dies in the end of the story. There is a man who helps and brings the boy with him. REFERENCES Ayres, Alex. 2005. The Wit and Wisdom of Mark Twain. New York: Harper & Row Publishers. Barrett, Marry. 2011. Celebrate: Just Live it. Bloomington: iUniverse. Beckham, Raymond, E. 2006. How to Help YourMissionary: A Guide for Parents of Missionaries, including Messages of Inspiration and Encouragement. Springville: Cedar Fort Publishing. Chang, Larry. 2006. Wisdom for the Soul. Washington: Gnosophia Publisher. Franklin, Jentezen. 2009. Fear Fighters: How to Live with Confidence in a World Driven by Fear. Florida: Charisma House. Gula, Richard M. 2007. Just Ministry. New jersey: Paulist Press. Haag, Ernest, Van Den. Passion and Social Constraint. Piscataway: Transaction Publishers. Hannus, Mufid James. 2002. Becoming Good Parent: An Existential Journey. New York: State University of New York Press. House, Paul. R. 1995. 1, 2 Kings: Vol. 8. United State of America: Broadman & Holman Publishers. Marcus, Paul. 2013. In Search of the Spiritual. London: Karnac Books Ltd. McCarthy, Cormac. 2006. The Road. New York: Vintage Books Pincot, J. 2007. Excellence: How to be The Best You can be by Those who Know. London: Marshall Cavendish Limited. Putman, Daniel. 2004. PsychologicalCourage: United State of America: University Press of America. Scarre, Geoffrey. 2010. On Courage: Thinking in Action. New York: Routledge. Thiessen, Delbert, D. 1996. Bittersweet Destiny: The Stormy Evolution of Human Behavior. Piscataway: Transaction Publishers. Vinci, Vincent. 2000. A Single Raindrop. Bloomington: iUniverse. Webster, Jerry A. 2012. What Brings A Soldier To His Knees. Bloomington: WestBow Press.